ISOLATION AND CHARACTERIZATION OF CYANOBACTERIA POSSESSING ANTIMICROBIAL ACTIVITY FROM THE SUNDARBANS, THE WORLD'S LARGEST TIDAL MANGROVE FOREST(1) - Pramanik, Arnab (Journal of phycology, 2011)
© 2011 Phycological Society of America.